Does structurally-mature dengue virion matter in vaccine preparation in post-Dengvaxia era? - Jedhan Ucat Galula; Gielenny M. Salem; Gwong-Jen J. Chang; Day-Yu Chao (Taylor & Francis Group, 2019)
The unexpectedly low vaccine efficacy of Dengvaxia®, developed by Sanofi Pasteur, and a higher risk of severe diseases after vaccination among dengue-naive children or children younger than 6 years old, have cast skepticism about the safety of dengue vaccination resulting in the suspension of school-based immunization programs in the Philippines. The absence of immune correlates of protection from dengue virus (DENV) infection hampers the development of other potential DENV vaccines. While tetravalent live-attenuated tetravalent vaccines (LATVs), which mimic natural infection by inducing both cellular and humoral immune responses, are still currently favored, developing a vaccine that provides a balanced immunity to all four DENV serotypes remains a challenge. With the recently advanced understanding of virion structure and B cell immune responses from naturally infected DENV patients, two points of view in developing a next-generation dengue vaccine emerged: one is to induce potent, type-specific neutralizing antibodies (NtAbs) recognizing quaternary structure-dependent epitopes by having four components of vaccine strains replicate equivalently; the other is to induce protective and broadly NtAbs against the four serotypes of DENV with a universal vaccine. This article reviews the studies related to these issues and the current knowledge gap that needs to be filled in.